Environmental versus analytical variability in exposure measurements - Nicas, M; Simmons, B P; Spear, R C (American Industrial Hygiene Association journal, 1991)
Measurements of 8-hr time-weighted average (TWA) exposures are subject to environmental variability and collection and analytical error. Environmental variability can be represented by the geometric standard deviation (GSD) of the lognormally distributed 8-hr TWAs; analytical variability can be represented by the coefficient of variation (CV) of the normally distributed collection and analytical errors. A mathematical expression is derived for the variance of the measured 8-hr TWAs as a function of the GSD of the true daily average exposures and the total CV of the industrial hygiene method used in monitoring. For typical values of the GSD and CV, environmental variability is far more important than analytical variability in determining the variance of the measured 8-hr TWAs. A resulting policy implication is that the Occupational Safety and Health Administration inappropriately focuses on analytical variability when determining compliance with its permissible exposure limits.